Systematic Literature Review: Metacognitive Strategy In Science Learning - Anggia Rose Sukaton; Parlan Parlan; Hayuni Retno Widarti; Sri Rahayu; I Wayan Dasna (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
The purpose of this review article was to understand the application of metacognitive strategies in science education as well as identify the syntax of these strategies and their impact on the studied variable. The method used was called a systematic literature review (SLR), and it consisted of three steps: planning, carrying out, and reporting. The process of searching and filtering articles was carried out using the PRISMA method in electronic journals. Sixteen articles were relevant to the research goal and were published in twelve journals (Scopus). The results of the study indicated that students were most often used as research subjects in metacognitive strategy research. Most articles on metacognitive strategy in science learning were published in 2019, and quasi-experimental research designs were most frequently used. Chemistry is the scientific discipline that uses this strategy the most. The main metacognitive strategy syntax had three stages: planning, implementing learning, monitoring, and evaluating. The most researched metacognitive strategy has an influence on improving student learning outcomes. Therefore, metacognitive strategies could be a choice for teachers in schools to improve student learning outcomes in science. Metacognitive strategies still have great opportunities to be developed and applied in science learning in the future.